2006
DOI: 10.1159/000100404
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Protein C, Protein S and Cytokines in Acute Ischemic Stroke

Abstract: Objective: The role of inflammation in the pathogenesis of acute ischemic stroke is well known, but its association with the clinical picture is as yet unclear. Material and Methods: In our study, we measured the serum levels of the proinflammatory cytokines interleukin-1β (IL-1β), tumor necrosis factor α (TNFα) and interleukin-6 (IL-6) within the first 50 h of stroke in 60 acute stroke patients, and examined the association with the natural anticoagulants protein C and free protein S. We compared the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
5
1
3
Order By: Relevance
“…Despite the fact that in one study, lower PC serum levels were found to have a definite correlation with stroke severity in a group of 43 patients [14], the same correlation could not be found in our previous study [25]. In the present study, there was no correlation between stroke severity and PC.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Despite the fact that in one study, lower PC serum levels were found to have a definite correlation with stroke severity in a group of 43 patients [14], the same correlation could not be found in our previous study [25]. In the present study, there was no correlation between stroke severity and PC.…”
Section: Discussioncontrasting
confidence: 96%
“…In those studies, natural anticoagulants were studied simultaneously, but their association with insulin resistance and stroke severity has not yet been examined. We have previously shown a positive correlation between PS levels and stroke severity [25]. In another study, AT III level on admission showed significant correlation with stroke severity and disability at 3 months but not in the acute phase [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of both protein S and C4BP in the liver appears to be controlled by inflammatory mediators, including IL-6 (42,43). Levels of protein S are reduced in patients with ischemic stroke (44) and in patients with sepsis (45), possibly via the effects of TNF on endothelial cells (46). In contrast, glucocorticoids have been reported to elevate levels of protein S (47).…”
Section: Discussionmentioning
confidence: 99%